Age-Dependent Differences in the Rate and Symptoms of TIA Mimics in Patients Presenting With a Suspected TIA to a Neurological Emergency Room - Ippen, Franziska Maria; Walter, Fabian; Hametner, Christian; Gumbinger, Christoph; Nagel, Simon; Purrucker, Jan C.; Mundiyanapurath, Sibu (Frontiers in Neurology, 2021)
Background: Transient ischemic attack (TIA) needs further diagnostic evaluation to prevent future ischemic stroke. However, prophylaxis can be harmful in elderly if the diagnosis is wrong. We aimed at characterizing differences in TIA mimics in younger and older patients to enhance diagnostic accuracy in elderly patients. Methods: In a dedicated neurological emergency room (nER) of a tertiary care university hospital, patients with transient neurological symptoms suspicious of TIA (<24h) were retrospectively analyzed regarding their final diagnoses and their symptoms. These parameters were compared between patients aged 18-70 and >70 years using descriptive,univariable and multivariable statistics. Results: From November 2018 until August 2019, 386 consecutive patients were included. 271 (70%) had cardiovascular risk factors and all patients received cerebral imaging, mostly CT (376(97%)). There was no difference in the rate of diagnosed TIA between the age groups (85 (46%) vs. 58 (39%); p=0.213).TIA mimics in the elderly were more often internal medicine diseases (35 (19%) vs. 7 (5%); p<0.001) and epileptic seizures (48 (26%) vs. 24 (16%); p=0.032) but less often migraine (2 (1%) vs. 20 (13%); p<0.001). The most frequent symptoms in all patients were aphasia and dysarthria (107 (28%) and 92 (24%)). Sensory impairments were less frequent in elderly patients (23 (11%) vs. 54 (30%); p<0.001). Impaired consciousness and orientation were independent predictors for TIA mimics (p<0.001) whereas facial palsy (p<0.001) motor weakness (p<0.001), dysarthria (p=0.022) and sensory impairment (p<0.001) were independent predictors of TIA. Conclusion: TIA mimics in elderly patients are more likely to be internal medicine diseases and epilepsy compared to younger patients. Excluding internal medicine diseases seems to be important in elderly patients. Facial palsy, motor weakness, dysarthria and sensory impairment are associated with TIA.